Obraz Krakowa w języku poetyckim Wincentego Byrskiego - Olma, Marceli (ANNALES UNIVERSITATIS PAEDAGOGICAE CRACOVIENSIS. STUDIA LINGUISTICA, 2019)
The material basis of the paper is an unpublished collection of 47 sonnets by Wincenty Byrski, a poet from Podbeskidzie region. The author of the study discusses the language level of the poems (mainly lexis) in order to reconstruct the picture of Cracow preserved in the texts. According to the analysis, the poet used vocabulary and morphological forms which were known in the Polish language in previous centuries, as well as pompous lexis. Description of architectonic objects and other urban landscape elements was accompanied by their evaluation, which reflected historiosophy and the system of moral values, preferred